Combined application of gasification filter cake and Portulaca oleracea to promote soil quality and tomato yields under irrigation with brackish water - Wenlu Wei; Yanming Gao; Huiru Wang; Yune Cao; Jianshe Li (Horticultural Plant Journal, 2025)
Brackish water (BW) irrigation may cause soil quality deterioration and thereby a decrease in crop yields. Here we examined the impacts of applying gasification filter cake (GFC), intercropping with Portulaca oleracea (PO), and their combination on soil quality, nutrient uptake by plants and tomato yields under BW irrigation. The treatments evaluated included (i) freshwater irrigation (Control), (ii) BW irrigation, (iii) GFC application under BW irrigation (BW + GFC), (iv) intercropping with PO under BW irrigation (BW + PO), and (v) the combined application of GFC and PO under BW irrigation (BW + PO + GFC). Overall, the use of BW for irrigation resulted in a decline in both soil quality (assessed by a soil quality index (SQI) integrating a wide range of key soil properties including salinity, nutrient availability and microbial activities) and crop yields. Nevertheless, when subjected to BW irrigation, the application of GFC successfully prevented soil salinity. Additionally, the intercropping of PO decreased the soil sodium adsorption ratio and improved the absorption of nutrients by plants. As a result, the BW + GFC + PO treatment generally showed higher tomato yield as compared to other BW-related treatments (i.e. BW, BW + GFC and BW + PO). Compared to BW, the BW + GFC + PO treatment had an average increase of 24.7% in the total fruit yield of four Cropping Seasons. Furthermore, the BW + GFC + PO treatment consistently exhibited the highest fruit quality index (FQI). Taken together, the combined application of GFC and PO is effective in promoting soil quality and crop yields under BW irrigation.